REVERSE LOGISTICS ON THE WAY TO SUSTAINABILITY - Feitoza Garcia, Bruno Rafael; Bertaci, Moacir José (Revista Interface Tecnológica, 2020)
The problem with work is thinking about future generations and prioritizing the environment. What is reverse logistics? Specific objective is to study and describe reverse logistics and its benefits for the company’s operations. For this reason, it is necessary to study the correlation between reverse logistics and business strategy, with the purpose of emphasizing the material return system as a principle of conquering competitive advantage for a company, and how strategy and efficiency the organization can be fundamental. The databases will be used as an example: SCIELO and BIREME, books and magazine articles, the subject being addressed using the keywords. It was found that there are strategies to identify new forms of reuse and recycling of waste that can enable the formation of new reverse channels.